Pelatihan Keterampilan Ibu untuk Deteksi Perkembangan Anak Prasekolah Menggunakan Kuesioner Pra Skrining Perkembangan - Siti Yulaidah; Ayesha Hendriana Ngestiningrum; Tutiek Herlina; Astin Nur Hanifah (FORIKES, 2023)
Monitoring the development of pre-school children during the Covid-19 pandemic cannot take place optimally, so parents can be trained to do this. The purpose of this study was to analyze the effectiveness of the “Bulan Si Kembang” (Smart Mothers in Development Detection) training to improve mothers' skills in early detection of child development using KPSP (Child Development Pre Screening Questionnaire). The research design was one group pre-test and post-test. The samples were 42 guardians of pre-school children, who were selected by simple random sampling technique. The independent variable was the